On line bisection: Validity and reliability of online measures of pseudoneglect. Issue 4 (4th July 2022) - Mitchell, Alexandra G.; Kandt, Paulina O.; McIntosh, Robert D.
ABSTRACT: This study assessed pseudoneglect using line bisection and perceptual landmark tasks in two matched online sessions. Line bisection bias was characterized by the traditional measure of Directional Bisection Error (DBE), and by Endpoint Weightings Bias (EWB), derived from an "endpoint weightings" analysis, made possible by the independent manipulation of left and right endpoints. EWB is proposed to index the relative attentional allocation to the two ends of the line. The expected leftward bias (pseudoneglect) was found, with larger effect sizes for EWB ( d  = −0.34 in both sessions) than for DBE (−0.22 in Session 1 and −0.14 in Session 2). Although EWB was slightly less reliable than DBE, it was more sensitive to pseudoneglect, and the endpoint weightings method has further advantages, including the option of an additional measure of non-lateralized attention. A substantial proportion of participants had difficulty following the instructions for the landmark task, which highlights the need for clear instructions and performance checks for this task. This study shows that line bisection can be used to measure pseudoneglect online, and provides grounds to suggest that the task should routinely include the independent manipulation of left and right endpoints, so that an endpoint weightings analysis can be performed.